2022
DOI: 10.1021/acsnano.2c07627
|View full text |Cite
|
Sign up to set email alerts
|

Threats to Terrestrial Plants from Emerging Nanoplastics

Abstract: Nanoplastics are ubiquitous in ecosystems and impact planetary health. However, our current understanding on the impacts of nanoplastics upon terrestrial plants is fragmented. The lack of systematic approaches to evaluating these impacts limits our ability to generalize from existing studies and perpetuates regulatory barriers. Here, we undertook a meta-analysis to quantify the overall strength of nanoplastic impacts upon terrestrial plants and developed a machine learning approach to predict adverse impacts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…The results of a recent study using machine learning to predict phytotoxicity of NPs showed that the characteristic variable of plant species ranked second in relative contribution to overall model predictions (Dang et al, 2022), which is consistent with the analysis in this section. There is a large variation in the tolerance of different plants, which is reflected in studies with conventional pollutants (Kabata-Pendias, 2000).…”
Section: Plant Species and Growth Periodsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of a recent study using machine learning to predict phytotoxicity of NPs showed that the characteristic variable of plant species ranked second in relative contribution to overall model predictions (Dang et al, 2022), which is consistent with the analysis in this section. There is a large variation in the tolerance of different plants, which is reflected in studies with conventional pollutants (Kabata-Pendias, 2000).…”
Section: Plant Species and Growth Periodsupporting
confidence: 87%
“…(d) SHAP values of the variable features for all training set observations in the RF model in panel ‘a’. Reproduced with permission from Dang et al (2022). Copyright 2022 ACS Publications.…”
Section: Influencing Factors Of Np Phytotoxicitymentioning
confidence: 99%
“…316 meta-analysis and ML were used to investigate the impacts of nanoplastics on terrestrial plants. 146 This study revealed that toxicity metrics most affected adverse effects, followed by plant species, nanoplastic mass concentration, and nanoplastic size. Thus, ML is valuable for the ecological risk assessment of NMs and can also extract new knowledge from the algorithm decision-making process.…”
Section: Modeling Cellularmentioning
confidence: 88%
“…MNPs have been found in honey, sugar, and all sorts of fish (Devriese et al, 2015). After plant species, mass concentration and size of nanoplastics, exposure period and pathway, negative effects are most frequently linked to toxicity measures (Dang et al, 2022). Analysis of tap, bottled, and spring waters using FTIR spectroscopy revealed the presence of microplastics in all of these water sources (Yee et al, 2021).…”
Section: Origins Fates and Occurrence In The Food Chainmentioning
confidence: 99%